OGLE-2014-BLG-0289: precise characterization of a quintuple-peak gravitational microlensing event - Udalski, Andrzej; Hundertmark, Markus; Schmidt, Robert W.; Wambsganß, Joachim (The astrophysical journal, 2018)
We present the analysis of the binary-microlensing event OGLE-2014-BLG-0289. The event light curve exhibits five very unusual peaks, four of which were produced by caustic crossings and the other by a cusp approach. It is found that the quintuple-peak features of the light curve provide tight constraints on the source trajectory, enabling us to precisely and accurately measure the microlensing parallax ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn1.gif] $π _\rmE$ . Furthermore, the three resolved caustics allow us to measure the angular Einstein radius ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn2.gif] $þeta _\rmE$ . From the combination of ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn3.gif] $π _\rmE$ and ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn4.gif] $þeta _\rmE$ , the physical lens parameters are uniquely determined. It is found that the lens is a binary composed of two M dwarfs with masses ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn5.gif] $M_1=0.52± 0.04\ M_ødot $ and ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn6.gif] $M_2=0.42± 0.03\ M_ødot $ separated in projection by ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn7.gif] $a_\perp =6.4± 0.5\,\mathrmau$ . The lens is located in the disk with a distance of ##IMG## [http://ej.iop.org/images/0004-637X/853/1/70/apjaaa295ieqn8.gif] $D_\rmL=3.3± 0.3\,\mathrmkpc$ . The reason for the absence of a lensing signal in the Spitzer data is that the time of observation corresponds to the flat region of the light curve.